Increasing Reading and Writing Interest of Mentally Disabled Students Through Picture Media: Peningkatan Minat Baca Tulis Siswa Tunagrahita Melalui Media Gambar - Melati, Putri Elni; Sriyani, Dartik; Novita, Delia; Yuliyanti, Silvina; Ruby, Arcivid Chorynia (Madrosatuna: Journal of Islamic Elementary School, 2023)
Children with mental retardation are in groups below normal or slower than average, both in social development and intelligence. This study aims to improve the process and results of the ability to read and write for moderately mentally disabled children in class IIC1 at SLBN Kaliwungu Kudus. Group Design. The research subjects were one mentally retarded student with a sample of 1 class with mild mental retardation class IIC1, parents, and homeroom teacher class IIC1. Data collection techniques using observation and tests. This study uses data collection techniques from observations of the subject. The data analysis technique in this study is a quantitative experiment. The results showed an increase in the process and development of the literacy skills of students with mild mental retardation. The learning process indicated the process improvement by the lesson plan. Being written, as well as being able to write simple sentences to improve reading and writing in students. The results showed that picture media effectively increased the ability and interest in writing and reading in mentally disabled students in class II C1 SLBN Kaliwungu by obtaining an average pretest result of 0.65 and an average post-test of 0.47.